The joint effects of apolipoprotein B, apolipoprotein A1, LDL cholesterol, and HDL cholesterol on risk: 3510 cases of acute myocardial infarction and 9805 controls. - Parish, S; Peto, R; Palmer, A; Clarke, R; Lewington, S; Offer, A; Whitlock, G; Clark, S; Youngman, L; Sleight, P; Collins, R (Oxford University Press, 2009)
AIMS: Plasma levels of apolipoprotein B (apoB), the main surface protein on LDL particles, and LDL-C, the amount of cholesterol in those particles, are closely correlated and, considered separately, are positive risk factors. Plasma levels of apolipoprotein A(1), the main surface protein on HDL particles, and HDL-C, the amount of cholesterol in those particles, are also closely correlated with each other and, considered separately, are negative risk factors. The interdependence of these four risk factors is unclear. METHODS AND RESULTS: Case-control study among 3510 acute myocardial infarction patients (without prior vascular disease, diabetes, or statin use) in UK hospitals and 9805 controls. Relative risks (age, sex, smoking, and obesity-adjusted) were more strongly related to apoB than to LDL-C and, given apoB, more strongly negatively related to apoA(1) than to HDL-C. The ratio apoB/apoA(1) was uncorrelated with time since symptom onset in cases, was reproducible in samples collected a few years apart in controls (correlation 0.81), and encapsulated almost all the predictive power of these four measurements. Its effect was continuous, substantial throughout the UK normal range [relative risk, top vs. bottom decile of this ratio, 7.3 (95% CI 5.8-9.2)] and varied little with age. The ratio apoB/apoA(1) was substantially more informative about risk (chi(1)(2) = 550) than were commonly used measures such as LDL-C/HDL-C, total/HDL cholesterol, non-HDL cholesterol, and total cholesterol (chi(1)(2) = 407, 334, 204, and 105, respectively). Given apoB and apoA(1), the relationship with risk of LDL-C was reversed, and this reversal was strengthened by appropriate allowance for random measurement errors in two correlated variables. Given usual apoB, lower LDL-C (consistent with smaller LDL particles) was associated with higher risk (P < 0.0001). During the first 8 h after symptom onset HDL-C increased by about 10%, precluding reliable assessment of the joint relationship of apoA(1) and pre-onset HDL-C with risk in such retrospective case-control studies. CONCLUSION: Apolipoprotein ratios are more informative about risk than lipid fractions are. This suggests that, among lipoprotein particles of a particular type (LDL or HDL), some smaller and larger subtypes differ in their effects on risk. Direct measurements of even more specific subtypes of lipoprotein particles may be even more informative about risk.